2012
DOI: 10.1136/sextrans-2011-050355
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of a rapid point-of-care test for detection ofChlamydia trachomatisamong women in a clinical setting

Abstract: Objectives To compare the effectiveness and cost-effectiveness of a promising new point-of-care (POC) chlamydia test with traditional nucleic acid amplification testing (NAAT), and to determine the characteristics that would make a POC test most cost-effective. Methods A decision tree was constructed to model chlamydia screening visits to a sexually transmitted disease clinic by a hypothetical cohort of 10 000 women. The model incorporated programmatic screening costs, treatment costs and medical costs avert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 29 publications
1
65
1
1
Order By: Relevance
“…A recent review of available POC tests for detection of STIs reported disappointing sensitivity for tests for Chlamydia (3). A recent cost-effectiveness study has demonstrated that implementation of POC tests meeting the ASSURED criteria can be cost-effective, compared with traditional NAATs (48). Additionally, a POC test with moderate sensitivity (65%) can help to treat more Chlamydia-positive cases than a NAAT alone when the rate of patients returning for results and treatment is lower than 65% (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of available POC tests for detection of STIs reported disappointing sensitivity for tests for Chlamydia (3). A recent cost-effectiveness study has demonstrated that implementation of POC tests meeting the ASSURED criteria can be cost-effective, compared with traditional NAATs (48). Additionally, a POC test with moderate sensitivity (65%) can help to treat more Chlamydia-positive cases than a NAAT alone when the rate of patients returning for results and treatment is lower than 65% (49).…”
Section: Discussionmentioning
confidence: 99%
“…The Clearview Chlamydia immunoassay test (Inverness, Princeton, NJ) has been primarily evaluated against culture, and lack of sensitivity has been reported repeatedly (48). The Chlamydia Rapid Test has shown promising results for the sensitive detection of C. trachomatis in 25 min (50).…”
Section: Discussionmentioning
confidence: 99%
“…The hands-on time is approximately 5 min and the time for results is quick (Ͻ2 h) compared to other NAAT platforms. The ability to provide test results and treat patients before they leave the clinic or doctor's office has substantial potential to reduce complications and it might be cost-effective depending on the cost of the assay, the time patients are willing to wait, and the number of patients who might not return to a clinic for their result (3,4,24).…”
Section: Discussionmentioning
confidence: 99%
“…Since the previous literature review [7], 4 studies have been published on the performance of investigational CT POC tests [64][65][66][67]. Hesse et al evaluated the performance of 4 novel CT POC prototypes in succession, each modified based on communication with the manufacturer, on vaginal and cervical swabs compared with SDA [64].…”
Section: Discussionmentioning
confidence: 99%